Tank Cleaning Process Optimization For Loading Tanks MT Bauhinia Guna Cargo Change - Tonia, Febrio Adha; Arleiny, Arleiny; Lestari, Elise Dwi (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2023)
Suboptimal implementation of tank cleaning will produce suboptimal results and can affect loading failure. These less than optimal results are influenced by several things. Tank Cleaning is a tank cleaning carried out on a tanker which serves to reduce the risk of damage to the cargo. Wall wash test is a tank cleanliness test for chemical tankers after completing tank cleaning. In the loading process, chemical tankers must prepare their loading tanks in accordance with the correct procedures. In every process of preparing this tank must always pay attention to the standards that have been determined from the surveyor or based on IMO (International Maritime Organization). When the Chemical ship will load, the ship's tank will be checked by the cargo surveyor, if there is dirt or residual cargo before the ship can be declared a failure in the tank cleaning process and as a result the ship will be ordered out of the Jetty, ordered to re-clean. This causes company losses because there will be delays in the loading and discharging process of the ship and the company gets complaints from the charter party. The method used to carry out the research is descriptive qualitative. Cutting the time for tank cleaning can result in poor tank cleaning results, poor quality materials also result in less than optimal results, and equipment that lacks maintenance will result in less than optimal tool performance. When the Chemical ship will load, the ship's tank will be checked by the cargo surveyor, if there is dirt or residual cargo before the ship can be declared a failure in the tank cleaning process and the ship will be ordered out of the Jetty and ordered to re-clean. This causes losses to the company because there will be delays in the loading and discharging process of the ship and the company can get complaints from the charter party. The success or failure of tank cleaning and wall wash tests depends on the discipline of the crew, adequate tools and materials, and procedures that are carried out properly.